تأثير تقنية التخريش على قوة الارتباط العاجي لنظامين مختلفين من المواد الرابطة للراتنج المركب (دراسة مخبرية) - ونوس محمد (Latakia University Journal -Medical Sciences Series, 2018)
Aim: The aim of this study is to compare the the effect of etching techniaue on bonding strength to dentin of two composite bonding systems . Materials and Methods: 40 freshly human upper premolars extracted due to orthodontic reasons , non carious, unrestored. Then they divided into two groups (A,B). After exposing the dentin of the occlusal surface, we applied the total etch bonding system (Excite f) to group A and self etch bonding system (tetric N-bond self etch) to group B then teeth were applied in acrylic resin blocks. Bonding strength were determind using shear bond strength test. Results were evaluated statistically using T student test (P<0.05). Results: the study showed that there were no statistically significant differences of bonding strength to dentin between the total etching and self etching systems of composite bonding agents. الهدف :يهدف هذا البحث إلى مقارنة تأثير تقنيتين مختلفتين للتخريش الحمضي على شدة الارتباط إلى العاج في المنطقة الخلفية لنظامين من المواد الرابطة للكمبوزت. المواد والطرق : تألفت العينة من 40 ضاحكاً علوياً بشرياً مقلوعاً حديثاً لأسباب تقويمية, خالية من أي نخر أو ترميم سابق , قسمت العينة عشوائياً إلى مجموعتين كل مجموعة مؤلفة من 20سناً, بعد كشف العاج الطاحن للأسنان, تم في المجموعة الأولى تطبيق مادة رابطة ذات نظام التخريش الكلي (Excite f) total etching وفي المجموعة الثانية مادة رابطة ذاتية التخريش tetric N-bond self etch)) و من ثمّ يتم الترميم باستخدام الراتنج المركب tetricNceram. تم غرس الأسنان ضمن قوالب إكريلية ليتم اختبار العينة باستخدام جهاز اختبار قوى القص بتطبيق حمولة حتى انهيار الترميم. حلّلت النتائج إحصائياً بتطبيق اختبار T Student للعينات المستقلة عند مستوى دلالة 0.05 % . النتائج: أظهرت نتائج البحث أنه لا توجد فروق دالة إحصائياً لقوة الارتباط العاجي بين تقنيتي التخريش الذاتي و الكلي في العاج على الأسنان الخلفية .